Resonant Leadership: A Catalyst for Job Empowerment Among Palestine Technical University Kadoorie Employees - Obied, Asem (Journal of Technical Education and Training, 2023)
The study aimed to identify the role of resonant leadership in promoting job empowerment among the employees of Palestine Technical University Kadoorie, with different variables: educational qualification, gender, staff, and experiences. The researcher designed a questionnaire addressed to employees consisting of 32 items distributed on four domains: resonant leadership (mindfulness, hope, empathy) and (career empowerment). The study used descriptive method. The sample consisted of 73 employees from PTUK, Ramallah branch, who were chosen randomly. The results showed that the employees’ responses were moderately on all domains. The results showed that there are no differences in the employees’ point of view according to the educational qualification variable in all domains, and there are differences in the employees’ opinions according to the gender variable in the domains of mindfulness, hope, and job empowerment in favor of male. The existence of differences in the opinions of employees, according to the variable of staff, in the domain of hope, empathy, and job empowerment in favour of academic employees. There are differences in the opinions of employees according to their experiences in the domains of (mindfulness and hope (in favour of employees with mindfulness (less than 5 years). The results also showed that there is a statistically significant positive correlation between resonant leadership and job empowerment. The study suggests that senior leaders and employees at PTUK should prioritize the use of resonant leadership to achieve job empowerment. It suggests ways to implement this approach among senior leaders and employees, which can benefit organizations seeking to enhance employee empowerment through effective leadership practices.